2013
DOI: 10.1002/asna.201211861
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray emission from RX J1720.1+2638 and Abell 267: A comparison between a fossil and a non‐fossil system

Abstract: We present the XMM-Newton X-ray analysis of RX J1720.1+2638 and Abell 267, a non-fossil and a fossil system, respectively. The whole spectrum of both objects can be explained by thermal emission. The luminosities found for RX J1720.1+2638 and Abell 267 in the 2-10 keV band are 6.20 −0.11 × 10 44 erg s −1 , respectively. The radial profiles show a cool core nature for the non-fossil system RX J1720.1+2638, while Abell 267 shows a constant behaviour of temperature with radius. Metallicity profiles have also been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…The mass and concentration posteriors are consistent with the well established M 200 − c 200 relation derived from N-body simulations (Dutton & Macciò 2014). The corresponding mass profile (Figure 10) is in good agreement with previously measured masses of A267 from X-ray and weak-lensing measurements (Jiménez-Bailón et al 2013;Okabe et al 2010), as well as the dynamical estimate based on the caustic technique (Rines et al 2013). Interestingly, the dynamical mass previously estimated directly from the galaxy velocity dispersion (assuming no sub-substructure; Rines et al 2013) is larger than we infer when we allow for N subs = 5 sub-populations, but in good agreement with the mass profile we obtain if we restrict our Jeans model to N subs = 0 sub-populations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mass and concentration posteriors are consistent with the well established M 200 − c 200 relation derived from N-body simulations (Dutton & Macciò 2014). The corresponding mass profile (Figure 10) is in good agreement with previously measured masses of A267 from X-ray and weak-lensing measurements (Jiménez-Bailón et al 2013;Okabe et al 2010), as well as the dynamical estimate based on the caustic technique (Rines et al 2013). Interestingly, the dynamical mass previously estimated directly from the galaxy velocity dispersion (assuming no sub-substructure; Rines et al 2013) is larger than we infer when we allow for N subs = 5 sub-populations, but in good agreement with the mass profile we obtain if we restrict our Jeans model to N subs = 0 sub-populations.…”
Section: Discussionsupporting
confidence: 89%
“…Like previous plots, the dark and light regions show the 68% and 95% confidence intervals of the PDFs, and the solid and dashed black curves show the median posterior and maximum likelihood velocity dispersion profiles, respectively. For comparison we include , respectively (Rines et al 2013), and in blue we show the X-ray derived mass M X 500 (Jiménez-Bailón et al 2013). Our results are consistent with M X 500 , M Caustic…”
Section: Results For A267supporting
confidence: 83%
See 1 more Smart Citation
“…Our smooth parametric fit shows a decrease in temperature in the outskirts at a significance of 11.8σ, and both our density and temperature profiles are in excellent agreement with the ACCEPT values. Jiménez-Bailón et al (2013) found a shock front with >16keV gas 2 NW of cluster, and this elongated cluster is possibly undergoing a large merger event (Boschin et al 2004). Further evidence for a major merger was detailed in Canning et al (2015), who used Chandra data to identify numerous cold and shock fronts, along with a large temperature spike ∼ 25 away from the core of the cluster.…”
Section: Discussionmentioning
confidence: 94%
“…Further contributions in the present conference summary volume by Marziani et al (2013), Jiménez-Bailón et al (2013), and Gu et al (2013) discuss various connections of cluster properties to the galaxy population in the clusters.…”
Section: Simulationsmentioning
confidence: 98%